Study The Application of Cleaner Production at Bukit Asam (Corporation) Tarahan Coal Terminal - Merza Rahmawati (Lembaga Penelitian dan Pengabdian Masyarakat (LPPM), Institut Teknologi Sumatera, Lampung Selatan, Lampung, Indonesia, 2018)
The process of accumulation (stockpiling) and mixing (blending) of coal will produce coal quality in accordance with the specifications you want, but as a byproduct of coal sludge typically generated, air pollution, water pollution, self combustion and others. Efforts in maintaining the quality of the coal in the process of stacking and blending of coal is by revamping operations in unit coal loading port. Approach to the prevention of waste offers the highest level of protection to workers and public health, including the protection and conservation of the environment both locally and globally. The research was conducted in two stages: (1) the observation and study of the cleaner production of coal at the terminal level, and (2) study the implementation of cleaner production and recommended for coal terminal. The results get 14 cleaner production options that can be implemented in Bukit Asam (Corp), Tarahan Coal Terminal 1). Garbage collection on each carriage. 2). The use of water from the inlet / sea water using water tankers. 3). Returns coal to stockpile. 4). Repeated use of water for watering the operational area. 5). Watering the carriage before the reversal process. 6). Installation of water spray / sprinkle. 7). Returns runoff water which still contains coal to the stockpile. 8). Make a wall in the dock. 9). Use a vacuum cleaner cars. 10). Collecting coal before the reversal process then sold to be used again as a raw material coal briquette plant. 11). Making holes biopori. 12). Soon handle spontaneous combustion. 13). Using mask and ear plugs. 14). The use of air monitoring equipment. The investment costs required for the implementation of cleaner production Rp. 2. 677.000.000, - which payedback period for 1 month.